Marriage of Different Religions in Indonesia in the Interfaith Fiqh Perspective (Building a Pluralist Inclusive Perspective). - Erwin Setyo Nugroho (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2019)
Since the beginning, Islam has always been faced with a religions plurality. The phenomenon is interfaith marriage. Some Ulama‟ have different opinion on marriage between religion believers. Some of them allow and the others forbid it. In this context, the urgency of this research is carried out. The writing of this thesis is very interested in studying interfaith marriages in the perspective of interfaith fiqh. Some sub- focus of this study are first, how is the interfaith marriage conception in the Islamic law perspective in legislation Indonesia and interfaith fiqh?. Second, How is the contextualization and dynamics of interfaith marriages for building a new perspective on pluralist inclusive fiqh in Indonesia? The two sub-studies will be assessed using the literature review approach. This study will use data and information with the help of material various kinds that contained in the library space such as books, magazines, texts, notes, stories, history, documents and others. Certainly, it is expected to find an overview of the main focus of the study selected. Based on several studies conducted, there are several conclusions that have been drawn up. These ara first, Interfaith Fiqh is the same as the hifd addzin rule, but its meaning is not fundamental to sectoral religious egos. hifd ad-dzin is meant more to safeguard the religious rights of Allah fellow creatures. Likewise with the same dar'ul mafasid that used in istinbath of general fiqh law. The intended Mafasid is defined as damage to human rights. Both of these containers are then generally oriented to grooving, starting with humanity and tolerance. Second, interfaith fiqh offers the legal istinbath concept which refers to the awareness of the necessity of multicultural life. The fiqh paradigm must be changed based on the benefit of multicultural social relations. Certain, in that society the value that must be upheld is inclusive and plural values. So it is right, if the inclusive pluralist paradigm becomes the methodological stand of Islamic law in the matter of interfaith marriage.